Green roofs – good regulatory practices with potential to be applied in Bulgaria and North Macedonia - Mariam Bozhilova; Miglena Zhiyanski; Biljana Stojanova; Plamen Glogov (Silva Balcanica, 2021)
Green roofs are used worldwide to mitigate the impacts of extensive urbanization, bringing benefits on social, economic, and environmental levels. In order to promote and facilitate the construction of green roofs by private investors, many countries have developed specific legislative requirements and incentives. However, there still are countries where the construction of green roofs is not properly addressed in the legislation, and where no incentive mechanisms are developed. The good practices in three European countries, leaders in regards to the implementation of green roofs – the Netherlands, Belgium, and Germany, are analyzed in this article. A variety of incentives is introduced to accelerate the construction of green roofs. Different requirements are also set to ensure that the roofs will be designed and maintained to provide the desired benefits. The existing local regulations in Bulgaria and North Macedonia were analyzed as well. The only incentive in Bulgaria is the possibility of reducing the legally required green area by compensating it with a green roof. In North Macedonia, no legislative documents or incentives related to green roofs were found.The regulations, applied in the Netherlands, Belgium, Germany, and other countries can be used as good practice examples, modified, and applied from the authorities of countries that still have not developed their own, in order to motivate the investors and facilitate the construction of green roofs.